ANALISIS FAKTOR YANG MEMPENGARUHI INSTRUMEN DERIVATIF SEBAGAI PENGAMBILAN KEPUTUSAN HEDGING (Studi Kasus Pada Sektor Infrastruktur, Utilitas dan Transportasi yang Terdaftar di BEI Pada periode 2011-2015) - Wijaya, Lutfi; Astuti, Pudji; Nugraha, Deni Pandu (JAB (Jurnal Akuntansi & Bisnis), 2018)
Hedging is an alternative of risk management that aims to protect the assets of company from losses caused by the risk. This study’s purpose is to analyze the influence of independent variables which include Debt to Equity, Growth Opportunity, Firm Size, Liquidity, and Institutional Ownership on hedging decision using derivative instruments at infrastructure, utility, and transportation companies listed on the Indonesia Stock Exchange in 2011-2015.Sample selection method used in this research is purposive sampling methodwith the provision of the company that publishes full financial statements in which 25 companies were included in the infrastructure, utility, and transportation companies as sample. This research used logistic regressions analysis technique, to find sets of variables that affect the probability the use of derivative instruments as hedging activities.The results of this study found that Debt to Equity, Growth Opportunity, Firm Size, Liquidity, and Institutional Ownershiphave significant effect on Hedging Decision using derivative instruments. From the results of logistic regression found that the variable Debt to Equity, Growth Opportunity, Firm Size, Liquidity, and Institutional Ownership for the different effect of companies to infrastructure, utility, and transportation companies can explain Hedging Decision using derivative instruments  by 54,2%, and the rest is explained by other variables outside the model. Keywords :          Derivative Instrument, Hedging, Debt to Equty, Growth Opportunity, Firm Size, Liquidity, Institutional Ownership